PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBANTUAN MEDIA INTERAKTIF WORDWALL UNTUK MENINGKATKAN HASIL BELAJAR PADA PEMBELAJARAN PENDIDIKAN PANCASILA DI KELAS V SD NEGERI 241 PALEMBANG - Dhea Rahma Dheni; Effendi Nawawi; David Saputra (JOURNAL SAINS STUDENT RESEARCH, 2024)
This study aims to apply the Problem Based Learning (PBL) learning model with the help of interactive Wordwall media to improve the learning outcomes of class V B students of SDN 241 Palembang. The method used is classroom action research (PTK) which is carried out from pre-cycle to cycle II. Each cycle consists of planning, implementation, observation, and reflection. Data were collected through learning outcome tests, observations, and interviews. The results showed that the application of PBL assisted by Wordwall can improve student engagement and their learning outcomes. The average student score in the pre-cycle was 26%, cycle I was 59%, increasing to 85% in cycle II. Observations showed an increase in student activity in the learning process, where students were more active in discussing and collaborating in solving problems. Thus, it can be concluded that the use of the PBL model supported by interactive Wordwall media is effective in improving the learning outcomes of class V B students of SDN 241 Palembang.